Sociodemographic and Lifestyle Determinants of Adherence to Current Dietary Recommendations and Diet Quality in Middle-Aged Spanish Premenopausal Women - Alonso-Cabezas, Marina; Pollán, Marina; Alonso-Ledesma, Isabel; Fernández de Larrea-Baz, Nerea; Lucas, Pilar; Sierra, Ángeles; Castelló, Adela; Pino, Marina Nieves; Pérez-Gómez, Beatriz; Martínez-Cortés, Mercedes; Lope, Virginia; Ruiz-Moreno, Emma (Frontiers in Nutrition, 2022)
Background: A healthy diet when approaching menopause could prevent some of the symptoms associated with the climacteric. Few studies examine adherence to current healthy dietary recommendations in middle-aged premenopausal women. Our objective was to analyze the diet quality and the adherence to the Spanish Society of Community Nutrition (SENC) dietary recommendations in middle-aged Spanish premenopausal women, and to identify the associated sociodemographic and lifestyle factors. Methods: This is a cross-sectional study based on 1251 premenopausal women, aged 39–50, who attended to Madrid City Council Medical Diagnostic Center. Women completed an epidemiological and a food frequency questionnaire. Degree of adherence to the SENC recommendations was estimated with a score that evaluated null (0 points) and full (1 point) adherence of each specific recommendation. Associations were explored using an ordinal logistic multivariable regression model. Results: Regarding food groups, the worst adherence was found for sweets, red/processed meat, olive oil and eggs. Most of the participants exceeded the recommended caloric intake from proteins and fats, and practically all of them showed vitamin D intake deficiency. The overall score ranged from 2 to 12 (out of 15), with a median of 6.0 (interquartile range: 5.0-7.0). Former smokers (OR: 1.38; 95%CI: 1.08-1.78), as well as those with higher educational level (ORSSecondary:1.68; 95%CI: 0.97-2.93, ORUniversity:1.82; 95%IC: 1.05-3.14), with two or more children (OR: 1.31; 95%IC: 1.00-1.72), with higher caloric intake (OR>2188.2kcal/day: 8.22; 95%CI: 6.19-10.92) and with greater physical activity (OR≥21 METS-h/week: 1.29; 95%CI: 0.95-1.76) showed greater adherence. Conclusions:Almost two-thirds of middle-aged premenopausal participants showed low or moderate compliance with SENC recommendations. Education, smoking, parity, and physical activity were associated with the degree of adherence to these recommendations.